2012
DOI: 10.1093/abbs/gms049
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dynamic culture of pre-osteoblasts seeded in HA-CS/Col/nHAP composite scaffolds and treated with α-ZAL

Abstract: Pre-osteoblast MC3T3-E1 cells were cultured in hyaluronic acid-modified chitosan/collagen/nano-hydroxyapatite (HA-CS/Col/nHAP) composite scaffolds and treated with phytoestrogen a-zearalanol (a-ZAL) to improve bone tissue formation for bone tissue engineering. Perfusion and dynamic strain were applied to three-dimensional (3D) cultured cells, which simulates mechanical microenvironment in bone tissue and solves mass transfer issues. The morphology of cell-scaffold constructs in vitro was then examined and mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…4 Collagen I provides a tissue-derived natural polymer; it is biocompatible and biodegradable and its mechanical and biological properties can be controlled and varied as required. 3,5 As a scaffold for bone regeneration, collagen can be used alone or in combination with various natural polymers and minerals that provide better representation of the extracellular environment, including hyaluronic acid-modified chitosan/collagen/hydroxyapatite composites 6 and collagen/hydroxyapatite scaffolds. 4 Although a number of studies have investigated osteoblasts cultured in 3D collagen gels, they mostly used microscopy for visual analysis of the osteoblast phenotype and alkaline phosphatase activity as a measure of osteoblast function.…”
Section: Introductionmentioning
confidence: 99%
“…4 Collagen I provides a tissue-derived natural polymer; it is biocompatible and biodegradable and its mechanical and biological properties can be controlled and varied as required. 3,5 As a scaffold for bone regeneration, collagen can be used alone or in combination with various natural polymers and minerals that provide better representation of the extracellular environment, including hyaluronic acid-modified chitosan/collagen/hydroxyapatite composites 6 and collagen/hydroxyapatite scaffolds. 4 Although a number of studies have investigated osteoblasts cultured in 3D collagen gels, they mostly used microscopy for visual analysis of the osteoblast phenotype and alkaline phosphatase activity as a measure of osteoblast function.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that constrained dynamic loading could strengthen bone structure and reduce bone fractures. Apparent strain (1,200 µε, 2,500-2,800 µε) can improve osteoblast proliferation and differentiation, increase osteoblast activity and counter osteoporosis in ovariectomized mice in vitro and MC3T3-E1 cells in vivo (30)(31)(32). In the present study, we first explored the effect of constrained dynamic loading in combination with CKIP-1 knockout in a tail suspension mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…23 The higher exposure of HA nanoparticles at the scaffold surface may result in significantly higher mineralization and enhanced bone formation 24 The osteogenic differentiation effect of CS have be mentioned in some literatures. [25][26][27][28][29] It has been reported that the combination of HA and CS can enhance bone regeneration and conductivity. 28 Wu et al 7 found that CS applied over the porous PLGA scaffold facilitated the differentiation of osteoblasts on the scaffold, possibly being an accelerator for such differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The osteoconductivity of the scaffold is positively correlated to the similarity of the nHA and natural bone minerals in composition, size, and morphology . The higher exposure of HA nanoparticles at the scaffold surface may result in significantly higher mineralization and enhanced bone formation The osteogenic differentiation effect of CS have be mentioned in some literatures …”
Section: Discussionmentioning
confidence: 99%